Anti-convulsant efficacy of long-acting injectable cannabidiol formulation (IVL5005) in the pentylenetetrazol-induced convulsions, with pharmacokinetic characterization - Youm, Soyoung; Cha, Joo Young; Lee, Slgirim; Seo, Young Dai; Park, Kun Hee; Song, Aeri; Park, Hyun-Je; Chan Son, Woo; Kim, Juhee (Frontiers in Pharmacology, 2025)
IntroductionCannabidiol (CBD) has demonstrated therapeutic potential in neurological disorders, particularly epilepsy. Epidiolex®, an FDA-approved oral CBD solution, is indicated for rare epileptic disorders such as Lennox–Gastaut syndrome and Dravet syndrome. However, its clinical utility is limited by rapid metabolism, short duration of action, and low oral bioavailability.MethodsTo address these limitations, we developed a long-acting injectable (LAI) formulation of CBD (IVL5005) using IVL-DrugFluidic® technology to achieve sustained and controlled drug release. CBD-loaded microspheres were manufactured and characterized by physicochemical analyses and in vitro release profiling. An in vivo pharmacokinetic study was conducted to evaluate systemic exposure following a single subcutaneous injection. The optimized formulation was selected for efficacy evaluation in a pentylenetetrazole (PTZ)-induced convulsion model.ResultsAll candidate formulations provided sustained systemic exposure for up to 4 weeks. The optimized IVL5005 formulation exhibited prolonged release with minimal initial burst. In the PTZ-induced convulsion model, IVL5005 demonstrated significant and durable anticonvulsant efficacy from a single dose, whereas the oral CBD solution produced only a transient effect. IVL5005 achieved a lower maximum plasma concentration compared with oral CBD solution, potentially reducing peak concentration-related adverse effects. No hepatic toxicity was observed with IVL5005, while liver changes were detected in the oral CBD group, likely due to extensive first-pass metabolism.DiscussionThese results indicate that IVL5005 may overcome key limitations of oral CBD and support its further development as a long-acting therapeutic option for epilepsy.